Administrative rationality in the logic of action of the officers of state enterprise - a study on the state of Santa Catarina companies - Cunha, Vera B. M. Carneiro da (1990)
This paper discusses the contraditory aspects of administrative rationality and the state-owned companies in Brazil. It also analyses the sort of rationality predominant in the logic of administrative action of the managers of these companies in the state of Santa Catarina, Brazil. The basic approach starts with the setting up of a typology involving three kinds of administrative rationality: private, public - complemental and public-social. The empirical verification was accomplished through non-experimental research involving fifteen companies and thirty-eight directors of these companies. Data was collected throught personally-applied questionnaires. A Likert-type scale was used to measure the three kinds of rationality. The results obtained showed a tendency toward the preponderance of public-social rationality, closely followed by public-complemental, thus countering the currents of opinion brought into focus in the theoretical reference which showed the existence of a privatist management ideology among the managers of state-owned companies in Brazil.